Exploring the activity of polyamine analogues on polyamine and spermine oxidase: methoctramine, a potent and selective inhibitor of polyamine oxidase. (1st January 2019) - Di Paolo, Maria Luisa; Cervelli, Manuela; Mariottini, Paolo; Leonetti, Alessia; Polticelli, Fabio; Rosini, Michela; Milelli, Andrea; Basagni, Filippo; Venerando, Rina; Agostinelli, Enzo; Minarini, Anna
Abstract: Fourteen polyamine analogues, asymmetric or symmetric substituted spermine (1 –9 ) or methoctramine (10 –14 ) analogues, were evaluated as potential inhibitors or substrates of two enzymes of the polyamine catabolic pathway, spermine oxidase (SMOX) and acetylpolyamine oxidase (PAOX). Compound 2 turned out to be the best substrate for PAOX, having the highest affinity and catalytic efficiency with respect to its physiological substrates. Methoctramine (10 ), a well-known muscarinic M2 receptor antagonist, emerged as the most potent competitive PAOX inhibitor known so far ( K i = 10 nM), endowed with very good selectivity compared with SMOX ( K i =1.2 μM vs SMOX). The efficacy of methoctramine in inhibiting PAOX activity was confirmed in the HT22 cell line. Methoctramine is a very promising tool in the design of drugs targeting the polyamine catabolism pathway, both to understand the physio-pathological role of PAOX vs SMOX and for pharmacological applications, being the polyamine pathway involved in various pathologies.